Oral cancer awareness in patients attending university dental clinics: A scoping review of Australian studies. (3rd October 2021) - Ramamurthy, P; Sharma, D; Thomson, P
Abstract: This scoping review was carried out to evaluate the important role Australian university‐based dental teaching clinics and dental students might have in promoting oral cancer awareness in their patients. Four Online database (PubMed, OVID, Scopus and Emcare) were searched for studies that assessed oral cancer awareness amongst patients attending Australian university‐associated (teaching) clinics. A total of five articles were retrieved for full‐text analysis. All studies showed significant variation in patient awareness and understanding regarding the principal risk factors associated with oral cancer development. Smoking was predominantly identified as a significant risk factor, but alcohol consumption was less frequently recognized as relevant. Non‐healing ulceration was most commonly identified as a symptom of concern, whilst red and/or white mucosal patches were infrequently recognized as potentially malignant conditions. Our review confirms that a significant lack of patient awareness regarding oral cancer risk and the signs /symptoms of early malignancy or potentially malignant disease exist in patients attending dental teaching clinics. Important opportunities exist to involve dental students proactively in raising oral cancer awareness, delivering smoking cessation interventions and safe alcohol consumption advice to their patients. Incorporation of established health educational models might deliver effective support for such student‐delivered patient education.